Hapkido sebagai Media Pendidikan Karakter Islami: Studi Internalisasi Nilai dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 9 Krui - Wahyu Tri Atmojo; Eti Hadiati; Agus Faisal Asyha (WISE Pendidikan Indonesia, 2026)
Character formation has become a central concern in Islamic Religious Education, particularly in supporting students’ internalization of moral values through learning experiences that extend beyond classroom instruction. This study aims to analyze the internalization of Hapkido values in Islamic Religious Education learning at SMP Negeri 9 Krui, with a particular focus on the impact of Hapkido values on students’ character and morality, students’ roles in integrating these values, and the supporting and inhibiting factors influencing the internalization process. This study employed a descriptive qualitative approach. The research was conducted at SMP Negeri 9 Krui, Pesisir Barat, Lampung, involving one teacher or Hapkido instructor and two students as the main informants. Data were collected through semi-structured interviews, observation, and documentation, and were subsequently analyzed through data reduction, data display, and conclusion drawing. The findings reveal that Hapkido values contribute to strengthening students’ honesty, discipline, responsibility, courage, perseverance, respect, courtesy, and self-control. Students also played an active role in integrating these values into learning activities, worship practices, social interactions, and broader school activities. The internalization process was supported by teacher guidance, school facilities, extracurricular activities, family support, and students’ willingness to improve themselves. However, it was still constrained by laziness, behavioral inconsistency, excessive joking, and limited emotional regulation among some students. This study implies that Hapkido can serve as an experiential medium for strengthening Islamic character education.